The Effect of Organizational Commitment and Employee Work Quality on Work Performance in Job Satisfaction Moderation at Bank Indonesia Representative Office in North Sumatra Province - Erni Winari; Isa Indrawan (International Journal of Management, Economic and Accounting, 2024)
Human resource management (HRM) is a field of study and practice that focuses on the management and management of human resources in an organization. The goal is to ensure that the organization has a qualified, motivated, and productive workforce to achieve its strategic goals. It is important for organizations to pay attention to human resources because the performance and success of the organization is highly dependent on the quality and productivity of the workforce. Investing in HR development can increase employee loyalty, increase retention, reduce recruitment and retraining costs, and improve overall efficiency and productivity of the organization. The results of this study are as follows: Job Satisfaction is not able to moderate the organization's commitment to Work Performance with the original sample value of 0.004 and p values of 0.486. Job Satisfaction can moderate and weaken Job Quality against Job Achievement with the original sample value of -0.173 and p values of 0.018. Job satisfaction had a positive and significant effect on Job Achievement with the original sample value of 0.495 and p values of 0.001. Organizational Commitment had a positive and insignificant effect on Work Performance with an original sample value of 0.098 and p values of 0.260. Work Quality had a positive and significant effect on Work Achievement with the original sample value of 0.203 and p values of 0.033.